Training participation of an aging workforce in an internal labor market - Christian Pfeifer; Simon Janssen; Philip Yang; Uschi Backes-Gellner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2010)
We use a long panel data set for four entry cohorts into an internal labor market to analyze the effect of age on the probability to participate in different training measures. We find that training participation probabilities are inverted u-shaped with age and that longer training measures are undertaken earlier in life and working career, respectively. These findings are consistent with predictions from a human capital model which incorporates amortization period and screening effects. Our results point to a market failure in the context of human capital investments to increase employability of older workers.
Keywords: J14; J24; M53; 330; age; human capital; internal labor markets; training; Weiterbildung; Altersgruppe; Ältere Arbeitskräfte; Bildungsverhalten; Bildungsinvestition; Interner Arbeitsmarkt; Deutschland